Geotechnical Properties of Residual Diyarbakir Basaltic Clay in Turkey - Mehmet Hayrullah Akyıldız; İlknur Yar (Advances in Civil Engineering)
Diyarbakir province mean rock formation is basaltic due to its location. Basaltic parent rocks release much silt or clay when imposed to chemical or physical weathering. The soils are residual in origin. In other words, they formed in situ where the basaltic parent rocks exist. They were not transported by means of wind or water. In this research, firstly, the properties of Diyarbakir basaltic clays were investigated from literature. After that, one soil sample from Kayapinar vicinity has been taken to laboratory to find index properties. The values from two different locations which are obtained from literature and values which are obtained from laboratory were compared. The results indicated that the three samples from different locations showed roughly the same index properties. As per the results, the clay is high plastic (CH), and it has swelling potential. In this thesis, design parameters of posttensioned slabs on ground under different climatic scenarios were found. The widely used method for slabs on ground under swelling soils is the Post-Tensioning Institute (PTI) method. In order to use this method, Thornthwaite moisture index is required. This index is used in geotechnical engineering to identify moisture flux boundary conditions for unsaturated soils and depth of active zone for expansive soils. This index has been found using water balance sheet tables for Diyarbakir. So as to find the future moisture index, water balance sheet tables have been formed finding the climate projection data for Turkey in literature. In this way, five moisture index values of Diyarbakir have been found for the current situation and with regard to representative concentration pathway (RCP4.5 and RCP8.5) scenarios for 2050. The parameters for the maximum differential swell (em) and the angular moisture change index (ym) for design procedure according to the PTI method were found for each moisture index. Results showed that the ym and em values increased when the Thornthwaite moisture index is reduced. Also results showed that the slab thickness is increased when moisture index is reduced. Considering the moisture index parameters for future values, Diyarbakir is likely to face arid climates in the future.